2014
DOI: 10.1155/2014/294149
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of NMDA Receptors in the Ventral Tegmental Area on Hormonal and Eating Behavior Responses to Stress in Rats

Abstract: Background. Stress and its consequences are among the causes of accidents. Objective. The effects of intraventral tegmental area (I-VTA) memantine on the plasma corticosterone and eating parameters disturbance induced by acute stress were investigated. Methods. Male Wistar rats (W: 250–300 g) were divided into control and experiential groups, each of which received memantine either intra-VTA or peripherally. One week after bilateral cannulation, the rats received memantine (1 and 5 μg/Rat) five min before elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Howbeit, Anderson reported that transient stress caused animals to received less food pellets by decreasing lever pressing that consequently led to their weight loss; however, after 14 days of stress, both measures returned to pre-stress levels. On the other hand, in other studies, it was shown that foot-shock stress resulted in decreased food intake in male rats [32,33]. In accordance with the current study [34], that was found an increased expression of orexigenic relaxin-3 and misbalanced HPA axis activity raised food intake in condition of chronic stress in female rats [35].Thus, it can be concluded that chronic stress leads to the increment of food intake in female rather than male rats.…”
Section: Discussionsupporting
confidence: 90%
“…Howbeit, Anderson reported that transient stress caused animals to received less food pellets by decreasing lever pressing that consequently led to their weight loss; however, after 14 days of stress, both measures returned to pre-stress levels. On the other hand, in other studies, it was shown that foot-shock stress resulted in decreased food intake in male rats [32,33]. In accordance with the current study [34], that was found an increased expression of orexigenic relaxin-3 and misbalanced HPA axis activity raised food intake in condition of chronic stress in female rats [35].Thus, it can be concluded that chronic stress leads to the increment of food intake in female rather than male rats.…”
Section: Discussionsupporting
confidence: 90%
“…However, MEM-treated animals had a similar mean body weight to that of stressed animals. These results suggest that different mechanisms may be involved in the control of anxiety and body weight in response to CRS [54].…”
Section: Discussionmentioning
confidence: 99%
“…First, stress can affect appetite (Bagheri Nikoo et al, 2014[ 2 ]; Halataei et al, 2011[ 37 ]; Ranjbaran et al, 2013[ 86 ]). This effect is related to involvement of either the ventral tegmental area (VTA), or the amygdala via N-methyl-D-aspartate (NMDA) glutamate receptors (Nasihatkon et al, 2014[ 80 ]; Sadeghi et al, 2015[ 94 ]). However, it should also be noted that nutrition patterns have effects on the response to stress (Ghanbari et al, 2015[ 31 ]), and this suggests a bilateral interaction between nutrition and stress.…”
Section: Stress and Gastrointestinal Complicationsmentioning
confidence: 99%